Professionality Study of Pharmacist for Pharmaceutical Care in Community Pharmacy at Samarinda City - Nur, Muhammad Ramadhan Ramadhan (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Services related to pharmaceutical preparations that a pharmacist offers to patients directly and ethically with the goal of improving patient health are referred to as pharmaceutical services. In order to allow pharmacists to provide pharmaceutical services in a professional manner, the government has taken steps to enable them, as stated in Minister of Health Regulation Number 35 of 2014 about Pharmaceutical Service Standards in Pharmacies. Using Minister of Health Regulation Number 35 of 2014 as a guide, this study aims to describe the pharmaceutical service practices that pharmacists in Samarinda City pharmacies perform. This study employs a qualitative descriptive research design. Data was gathered by looking at questionnaire answers, conducting interviews, and observing pharmacists in action. There were fifty-one pharmacists from the Samarinda City Pharmacy who answered the survey. According to the study's findings, pharmacists in Samarinda City pharmacies manage 80.93% of pharmaceutical supplies, medical equipment, and consumable medical materials in addition to 81.1% of clinical pharmacy services. All practical services performed comply with Minister of Health Regulation Number 35 of 2014 standards.